Viromes and surveys of RNA viruses in camel-derived ticks revealing transmission patterns of novel tick-borne viral pathogens in Kenya. Issue 1 (1st January 2021) - Zhang, You; Hu, Ben; Agwanda, Bernard; Fang, Yaohui; Wang, Jun; Kuria, Stephen; Yang, Juan; Masika, Moses; Tang, Shuang; Lichoti, Jacqueline; Fan, Zhaojun; Shi, Zhengli; et al.
ABSTRACT : Tick-borne viruses (TBVs) capable of transmitting between ticks and hosts have been increasingly recognized as a global public health concern. In this study, Hyalomma ticks and serum samples from camels were collected using recorded sampling correlations in eastern Kenya. Viromes of pooled ticks were profiled by metagenomic sequencing, revealing a diverse community of viruses related to at least 11 families. Five highly abundant viruses, including three novel viruses (Iftin tick virus, Mbalambala tick virus [MATV], and Bangali torovirus [BanToV]) and new strains of previously identified viruses (Bole tick virus 4 [BLTV4] and Liman tick virus [LMTV]), were characterized in terms of genome sequences, organizations, and phylogeny, and their molecular prevalence was investigated in individual ticks. Moreover, viremia and antibody responses to these viruses have been investigated in camels. MATV, BLTV4, LMTV, and BanToV were identified as viral pathogens that can potentially cause zoonotic diseases. The transmission patterns of these viruses were summarized, suggesting three different types according to the sampling relationships between viral RNA-positive ticks and camels positive for viral RNA and/or antibodies. They also revealed the frequent transmission of BanToV and limited but effective transmission of other viruses between ticks and camels. Furthermore, follow-up surveys on TBVs from tick, animal, and human samples with definite sampling relationships are suggested. The findings revealed substantial threats from the emerging TBVs and may guide the prevention and control of TBV-related zoonotic diseases in Kenya and in other African countries.